STUDI MIX METHOD TENTANG DINAMIKA INTERAKSI PEDAGOGIS PENDIDIK-ANAK DODIK DAN IMPLIKASINYA TERHADAP KUALITAS PEMBELAJARAN DI LINGKUNGAN SEKOLAH DASAR - Fitri Dwi Indriyani; Babang Robandi; Dwinova Indhira Putri (STKIP Subang, 2025)
The quality of pedagogical interaction between educators and students constitutes a crucial factor determining learning effectiveness in elementary schools, yet teacher-centered approaches continue to dominate Indonesian learning practices. This study aims to analyze pedagogical interaction patterns, identify factors influencing interaction dynamics, and describe their implications for learning quality at SDN Sukagenah, Ciasem District. The research employs a mix method approach with explanatory sequential design, involving 54 first-grade students through purposive sampling technique, utilizing structured observations and questionnaires for quantitative data collection, alongside in-depth interviews and participatory observations for qualitative data. Results indicate that majority of students experience moderate-category interactions with highest emotional support (M=3.38) but low instructional support (M=2.96), dominated by unidirectional patterns in 68% of learning sessions. Five determinant factors were identified: teacher pedagogical competence, high teacher-student ratio (1:27), facility limitations, students' socio-economic background, and authoritarian school culture. Significant positive correlations were found between interaction quality and learning achievement, particularly instructional support (r=0.523, p<0.01), with high-quality interaction students achieving N-gain of 0.389 compared to 0.176 in low-quality group. This research recommends pedagogical transformation toward dialogic-interactive learning, teacher competency enhancement through continuous training, teacher-student ratio optimization, and development of democratic school culture to support meaningful learning within the Merdeka Curriculum context.